Apseudomorph tanaidaceans (Crustacea: Peracarida) from mud-volcanoes in the Gulf of Cadiz (North-east Atlantic) - Blazewicz-Paszkowycz, Magdalena (2012)
Faunal collections from mud-volcano sites in the Gulf of Cadiz, at depths between 355 and 3061 m, have revealed a high diversity (and in some cases high density) of tanaidaceans. A previous paper has described some of the tanaidomorph species found. Records of apseudomorph species from deep-sea chemosynthetic habitats are almost non-existent. The present study reports on seven apseudomorph species from five different genera from this material; two of the species, one in each of the genera Sphyrapus and Pseudosphyrapus are new to science, although there was insufficient material available to describe fully the Pseudosphyrapus species. Two of the other species are reported herein for only the second time. A neo-type is erected for Apseudes setiferus Bacescu, and a lectotype for Sphyrapus malleolus Norman & Stebbing; these two, plus Atlantapseudes nigrifrons Bacescu and Fageapseudes retusifrons Richardson are redescribed. The habitus of Apseudes grossimanus is figured. None of the taxa appear to show any morphological features specifically adapted to the peculiar habitat around mud-volcanoes. The genus Collossella is relegated to the synonymy of Fageapseudes. The non-chemosynthetic-habitat-associated species Apseudes coriolis is moved to Taraxapseudes.